MicroRNA-34c-5p exhibits anticancer properties in gastric cancer by targeting MAP2K1 to inhibit cell proliferation, migration, and invasion - Ma, Qian; Zhao, Yuan; Li, Zhaojun; Gao, Wenwei; Xu, Yuanyi; Li, Bing; Huang, Yunning; Huo, Zhenghao (BioMed research international, 2022)
Purpose. Gastric cancer(GC)is one of the deadliest digestive tract tumors worldwide，existing studies suggest that dysregulated expression of microRNAs (miRNAs) plays an important role in the pathogenesis and progression of GC. This study aimed to investigate the expression, biological function, and downstream mechanism of miR-34c-5p in GC, provide new targets for gastric cancer diagnosis and treatment. Methods. The expression of miR-34c-5p in GC tissues and cell lines was examined by RT-qPCR. Cell wound healing, transwell and cell cloning assays were used to detect the effect of miR-34c-5p on the migration and invasion abilities, respectively, of GC cells. Western blot was performed to detect the expression of related proteins. Bioinformatics analysis was used to predict the binding of MAP2K1 to miR-34c-5p and the targeting relationship was confirmed by dual luciferase reporter assay. Results. The expression level of miR-34c-5p was significantly decreased in GC tissues and cell lines. miR-34c-5p overexpression inhibited migration, invasion, and colony formation of gastric cancer cells, the related protein E-cadherin expression was significantly increased and N-cadherin, vimentin, and PCNA expression were significantly decreased, while miR-34c-5p knockdown exerted the opposite effects. In addition, the targeting relationship between miR-34c-5p and MAP2K1 was predicted and confirmed, and further confirmed by rescue experiments that MAP2K1 alleviated the inhibitory effect of miR-34c-5p in GC. Conclusion. MiR-34c-5p is lowly expressed in GC, and it can target MAP2K1 to exert inhibitory effects on GC proliferation, invasion, and migration. These findings provide a promising biomarker and a potential therapeutic target for gastric cancer.